CONTENT CREATOR YANG BERKARAKTER BERDASARKAN ANALISIS VIDEO YOUTUBE NINGSIH TINAMPI - Yanuarita Kusuma; Herma Retno Prabayanti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Being a konten kreator has its own challenges because every day you must update the ideas and concepts of the content that will be presented. It's not uncommon to choose shortcuts by using sensations to get the audience's attention. Konten kreator is a profession that has emerged as a developing technology product. Anyone can become a konten kreator; the problem then is how the konten kreator can communicate messages to the public properly. There needs to be a strategy implemented so that uploaded content can have a positive impact on increasing the number of engagement or follower accounts on social media. This article will focus on examining communication strategies to become a good konten kreator using Ningsih Tinampi's Youtube content as a case study. This research was conducted using a qualitative approach with semiotic analysis methods, then to test the validity of this research. Then the research team will use data triangulation. The results of the study show that a verbal and non-verbal approach with character needs to be owned by a konten kreator. In addition, Ningsih Tinampi's communicator credibility is Terminal credibility, which is a combination of derived and initial that complement each other. This is a combination of forms of verbal and non-verbal communication messages that have been successfully shown in every YouTube content.